Institutionalizing the Culture of Critique in the Scientific Community with Which Paradigm or Scientific Foundation? Modernism, Postmodernism or Chaos-Complexity - Seyyed Mohammad Hossein; Sousan Keshavarz (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Although critique is the basis of personal and social growth and development, this issue has not become a dominant culture and logical process of the scientific community. This situation has many reasons. One of these reasons is the underlying assumptions or paradigms governing the scientific community. Therefore, the purpose of this article was to analyze the culture of critique and explain this culture based on three dominant scientific paradigms: Modernism, Postmodernism, and Chaos-Complexity. Therefore, the deductive reasoning method was used. The statistical population included all the books, articles, studies related to the subject, and the most possible sources were selected by purposive sampling method as samples. The information was collected by a checklist and was analyzed by a verbal and qualitative content analysis method. The findings show that Modernism only allows critique as a theoretical determination, which is a negative and superficial understanding, and incompatible with the nature of criticism. Thus, the culture of critique in this paradigm has not been formed and institutionalized. Postmodernism also does not provide an opportunity for critique. But Chaos-Complexity is a very suitable context for the formation, promotion, and institutionalization of the culture of critique. Because its features and assumptions provide a proper explanation for the concept, characteristics, and all conventions of criticism. Therefore, the formation, promotion, and institutionalization of the culture of critique requires a paradigm shift from Modernism and Postmodernism to Chaos-Complexity.